The Eye is Listening: Music-Induced Arousal and Individual Differences Predict Pupillary Responses - Gingras, Bruno; Marin, Manuela M.; Puig-Waldmüller, Estela; Fitch, W. T. (Frontiers in Human Neuroscience, 2015)
Pupillary responses are a well-known indicator of emotional arousal but have not yet been systematically investigated in response to music. Here, we measured pupillary dilations evoked by short musical excerpts normalized for intensity and selected for their stylistic uniformity. Thirty participants (15 females) provided subjective ratings of music-induced felt arousal, tension, pleasantness, and familiarity for 80 classical music excerpts. The pupillary responses evoked by these excerpts were measured in another thirty participants (15 females). We probed the role of listener-specific characteristics such as mood, stress reactivity, self-reported role of music in life, liking for the selected excerpts, as well as of subjective responses to music, in pupillary responses. Linear mixed model analyses showed that a greater role of music in life was associated with larger dilations, and that larger dilations were also predicted for excerpts rated as more arousing or tense. However, an interaction between arousal and liking for the excerpts suggested that pupillary responses were modulated less strongly by arousal when the excerpts were particularly liked. An analogous interaction was observed between tension and liking. Additionally, males exhibited larger dilations than females. Overall, these findings suggest a complex interplay between bottom-up and top-down influences on pupillary responses to music.